Urban Blue Spaces : Planning and Design for Water, Health and Well-Being. - Bell, Simon. (Taylor & Francis Group, 2021)
This book presents an evidence-based approach to landscape planning and design for urban blue spaces that maximises the benefits to human health and well-being. Over 200 full colour illustrations accompany the case study examples from geographic locations all over the world.